Association of ESR1 Mutations and Visceral Metastasis in Patients with Estrogen Receptor-Positive Advanced Breast Cancer from Brazil. (14th August 2019) - Reinert, Tomás; Coelho, Guilherme Portela; Mandelli, Jovana; Zimermann, Edinéia; Zaffaroni, Facundo; Bines, José; Barrios, Carlos Henrique; Graudenz, Marcia Silveira
Abstract : Mutations in the ESR1 gene ( ESR1m ) are important mechanisms of resistance to endocrine therapy in estrogen receptor-positive advanced breast cancer and have been recognized as a prognostic and predictive biomarker as well as a potential therapeutic target. However, the prevalence of ESR1m in real-world patients has not been adequately described. Therefore, we sought to evaluate the prevalence of ESR1m in metastatic samples from Brazilian patients with estrogen receptor-positive (ER+) advanced breast cancer previously treated with endocrine therapy. The presence of ESR1m was evaluated in formalin-fixed paraffin-embedded (FFPE) breast cancer tissue using real-time quantitative polymerase chain reaction (RT-qPCR). Mutations in codons 380, 537, and 538 of the ESR1 gene were analyzed. Out of 77 breast cancer samples, 11 (14.3%) showed mutations in the ESR1 gene. ESR1m were detected in a variety of organs, and the D538G substitution was the most common mutation. In visceral metastasis, ESR1m were detected in 25% (8/32) of the samples, whereas in nonvisceral metastasis, ESR1m were detected in 6.7% (3/45) of the samples. The odds of a sample with visceral metastasis having an ESR1 mutation is 4.66 times the odds of a sample of nonvisceral metastasis having an ESR1 mutation (95% CI: 1.13–19.27;p value = 0.0333). Our study indicates that the prevalence of ESR1m in samples from Brazilian patients with metastatic ER+ breast cancer is similar to that described in patients included in clinical trials. We observed an association of ESR1m with visceral metastasis.